Hybrid metaheuristic to solve job sequencing problem - Gustavo Erick Anaya - Fuentes; Héctor Rivera - Gómez; Oscar Montaño-Arango; José Ramón Corona-Armenta; Enrique Martínez-Muñoz (Institute of Advanced Engineering and Science, 2022)
In this article, the job shop scheduling problem was solved, which is considered as an NP - Hard problem, so it is difficult to solve. The proposed algorithm consists in the combination and adaptation of the nearest neighbor meta heuristics and iterated local search (ILS) to find optimal solutions. The proposed algorithm was evaluated by comparing the results with those presented in different instances and sizes of the literature. The results of the proposed method were close in high percentages to the best re sults and averages obtained by other methods in the literature and in some cases, they were improved. The above represents the feasibility of a new combination of efficient methods in solving task scheduling problems.